Playfulness and adolescence: mentalization and neuropsychoanalysis perspective - Kolev, Martin V. (Frontiers in Psychology, 2024)
The article attempts at conceptualising the basic principles of how adolescents develop, getting out of childhood and proceeding to enter young adulthood. The age period of adolescence is marked with intense emotional states, lines of thinking, beliefs and transitions that caregivers often face challenges making sense of or mirroring. Combining mentalization-based approaches with neuropsychoanalytic findings about how basic emotional systems governing playful behavior work can shed additional light into the communication channels and specificities therapists might consider when engaging in such endeavour.